Gels and gel beads comprising polyvinyl alcohol, polyurethane and an immobilizing agent
The combination of PU and PVA gels with additives and fibers addresses the weaknesses of PVA beads, creating stable gel beads for efficient wastewater treatment with reduced leakage and improved mechanical properties.
Patent Information
- Application Number
- JP2022560377
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-04-01
- Filing Date
- 2020-06-03
- Publication Date
- 2025-02-03
- Estimated Expiration
- 2040-06-03
AI Technical Summary
Existing methods for fixing microorganisms and enzymes in polymer gels, such as polyvinyl alcohol (PVA) beads, suffer from issues like weak physical structure, adhesive problems, chemical decomposition, and leakage, limiting their effectiveness and durability in applications like wastewater treatment.
A method involving the use of polyurethane (PU) and PVA gels, combined with additives like sulfate, phosphate, and borate, and enhanced with synthetic or natural fibers, is used to create stable gel beads with improved mechanical strength and reduced leakage, allowing for continuous processing.
The resulting gel beads exhibit enhanced stability, reduced leakage, and improved adhesion, enabling efficient and cost-effective treatment of wastewater and other applications by maintaining dispersion and filtration in manufacturing processes.
Smart Images

Figure 0007625282000011 
Figure 0007625282000012 
Figure 0007625282000013
Abstract
Description
CROSS-REFERENCE TO RELATED APPLICATIONS
[0001] This application claims the benefit of U.S. Provisional Patent Application No. 63 / 003,516, filed April 1, 2020, which is incorporated by reference in its entirety. [Technical field]
[0002] The present invention relates to gels and gel beads formed from polyvinyl alcohol (PVA), said gels and gel beads optionally comprising polyurethane (PU), methods for making the gels and gel beads, methods for immobilizing microorganisms, cells, enzymes and / or other materials in the gels and gel beads, and methods for using such gels and gel beads in applications. [Background technology]
[0003] The use of immobilized microorganisms and enzymes is considered as an alternative technology for wastewater treatment to replace traditional suspension sludge (SS) systems such as activated sludge systems (Dumitriu and Chornet, 1998). Entrapment of microorganisms and enzymes in polymer gels has been done before, but it had various drawbacks (Kuraray Co., Ltd., 2012; Aslam et al., 2018). For example, the use of PVA for immobilization had many drawbacks, such as a weak physical structure and significant adhesion problems. Leakage of PVA gel from the surface of the beads often occurred under mechanical agitation by water flow or aeration. Significant PVA biodegradation problems were caused by entrapped microorganisms such as denitrifying bacteria such as Pseudomonas. Such drawbacks result in a limited useful life of PVA gel beads (e.g., a few months depending on the application).
[0004] Modification of PVA gel beads includes modification of the chemical structure of PVA gel beads using acetalization (Kuraray Co., Ltd., 2012), etherification (Schmidt et al., 1934) or other modifications (Aslam et al., 2018). Although this functional group modification may make PVA gel beads stronger to resist microbial degradation, these attempts have several drawbacks: (1) they are not cost-effective and require large amounts of energy; (2) they may use aldehydes, especially glutaraldehyde, which are toxic to microorganisms; (3) common microorganisms cannot survive under the specific process conditions applied, e.g., pH<3 and temperatures 40°C-80°C; (4) the weak physical structure produced causes compaction in the filter; (5) the formation of gel beads still depends on alginate in calcium ion solution, etc. The structure of alginate is easily decomposed because the calcium ion in the center of the chelate is detached and replaced by phosphate in natural water, etc. In addition, alginic acid itself is easily decomposed by microorganisms, which serve as a carbon source.
[0005] Some previous reports proposed environmentally friendly modifications of the immobilization process using a specific PVA-boric acid method. Hwang proposed in U.S. Provisional Application No. 62856328 (June 3, 2019) that adding sodium chloride, calcium chloride, and magnesium sulfate at the end of the immobilization process would improve the surface strength and solve the adhesion problem. However, it could not prevent significant leakage of the PVA gel from the inside of the gel beads or the edges of the tadpole-shaped gel beads. This indicates that the main cause of the adhesion problem still exists and has not been solved. Hwang et al. described the development of ether-type anionic polyurethane (PU) gel beads in a 2014 utility patent (ROC Patent No. I425050). In the 2014 application, PVA was not mentioned in these gel beads. Previously, Hwang et al. (https: / / www.slideserve.com / tiara / pu-pva) presented PU / PVA immobilized cell beads in 2005. There is little discussion of PU / PVA immobilized cell beads and PU gel beads. The reason is that the resulting physical structure is very weak and not suitable for use as a filter or for other purification or processing methods.
[0006] U.S. Patent No. 5,290,693 (1994) discloses hardening of PVA gel beads by the addition of phosphates, however the gel beads disclosed therein may still leak because the gel beads are not sufficiently hardened when hardened using phosphates.
[0007] Thus, there is a need for improved methods to improve upon current methods of producing gels and gel particles for immobilizing substances (e.g., microorganisms such as bacteria and novel substances not previously immobilized). The methods can be improved by using less toxic chemicals, more efficient and cost-effective processes, and semi-continuous or continuous processes rather than batch processes. The final properties of the gels and gel particles can also be improved by providing (1) improved stability, (2) increased reactivity of the immobilized substance, (3) reduced leakage, (4) improved hardness and strength, etc. Summary of the Invention
[0008] Embodiments of the invention include improving the structure and properties (e.g., stability, hardness, reinforcement, harsh environment mitigation, reduced leakage) of PVA and / or PU / PVA gels and gel beads that contain immobilized substances. Embodiments of the invention also include novel and unobvious methods (e.g., continuous, efficient processes such as extruders) and apparatus for producing PVA and / or PU / PVA gels and gel beads. The gels and gel beads contain one or more immobilized substances, such as, for example, microorganisms (e.g., bacteria, algae, fungi, protozoa, etc.), cells, enzymes, and / or other materials (e.g., non-enzymes, other organisms, other chemicals such as soil, sludge, mixtures of purified / partially purified, or unpurified substances).
[0009] These gel, gel bead, method, and device embodiments can include several operations performed sequentially or in combination. These operations include forming a PVA slurry solution, and optionally combining a PU with the PVA to form a PU / PVA slurry solution. The PU, which is preferably an ether-type hydrophilic polyurethane, may or may not be heated prior to use or in the slurry solution. The phrase "slurry solution" is used to describe complex slurries and / or solutions with multiple components or phrases present only once or at different times (e.g., components and phrases present as slurries, powders, mixtures, solutions, precipitates, etc.).
[0010] These gel, gel bead, method, and device embodiments may include mixing one or more anions (e.g., anion releasing compounds) with a PVA and / or PU / PVA slurry solution to form a PVA gel and / or a PU / PVA gel. The one or more anions used (e.g., from an added anion releasing compound) may preferably include sulfate, phosphate, and / or borate anions, as well as other suitable anions or anion releasing chemicals, as will be apparent to one of skill in the art. These operations may be performed sequentially or in various combinations.
[0011] These gel, gel bead, method, and apparatus embodiments may optionally include mixing the PVA and / or PU / PVA slurry solution with an etherification compound that increases or promotes (e.g., catalyzes) the formation of ether groups, preferably sulfuric acid or another acid.
[0012] These gel, gel bead, method, and device embodiments mix one or more substances, such as microorganisms (e.g., bacteria, algae, fungi, protozoa, etc.), cells, enzymes, and / or other materials (e.g., non-enzymes, other organisms, other chemicals such as soil, sludge, refined / partially refined, or unrefined mixtures of substances) with a slurry solution, and then mix a boric acid solution with the slurry solution containing one or more immobilized substances to form a gel or gel beads. These operations can be performed in sequence or in combination. In certain applications, the environment of the slurry solution can be improved by avoiding harsh conditions. Thus, in certain applications (e.g., microorganisms, cells), the pH of the slurry solution is preferably greater than about pH 3, more preferably greater than about pH 5.5, and most preferably close to about pH 7. In other applications, different pH ranges may be useful.
[0013] The immobilization material is preferably a microorganism, a cell, an enzyme, a non-enzymatic chemical, sludge, or a mixture of these materials.
[0014] These gel, gel bead, method and apparatus embodiments further include the use of intermittent dripping devices known in the art, and preferably use an extrusion device to form beads or other shapes of gel. The operation of using an extrusion device to form beads or other shapes of gel is preferably performed as part of a semi-continuous or continuous process. The operation of forming the gel preferably spreads the gel onto a surface or support, such as a board, plate or reaction component for use in the process or method.
[0015] These gel, gel bead, method, and device embodiments further include mixing one or more hardening agents into the gel or gel beads containing the one or more immobilization substances. The one or more hardening agents include cations or cation releasing compounds, such as alkali metals, alkaline earth metals, other metal ions, and / or mixtures thereof. Alkali metals include Li + , Na + , K + and / or mixtures thereof. The alkaline earth metal is preferably Ca 2+ , Mg 2+ and / or mixtures thereof are preferred. Other metal ions that can be used are Al +3 , Fe 2+ , Fe +3 , Zn 2+ and Cu 2+ and / or mixtures thereof are preferred.
[0016] These gel, gel bead, method, and device embodiments optionally further include mixing one or more reinforcing agents into the gel or gel beads containing one or more immobilization substances. Preferably, any one or more reinforcing agents include fibers. Preferred fibers include synthetic fibers such as polyacrylic acid, polyvinyl acetate, polyacrylamide, and the like, and natural fibers such as algae, cellulose, pulp, cotton, linen, and / or mixtures thereof. These operations can be performed sequentially or in various combinations.
[0017] A preferred embodiment of the gel beads of the present invention is a gel bead consisting of a PVA gel and / or a PU / PVA gel, which includes cross-linked PVA units and cross-linked PU / PVA units; the gel bead includes one or more immobilized substances, such as (e.g., bacteria, algae), cells, enzymes, and / or other materials; the preferred size of the gel bead is about 2 mm to about 6 mm, more preferably about 3 mm to about 5 mm, and most preferably about 4 mm. The preferred gel beads have less than about 10% leakage of PVA or immobilized substances from the gel beads after one week of use in an application such as an aqueous solution treatment process. More preferably, less than about 1% leakage of PVA or immobilized substances from the gel beads after one week of use in an application such as an aqueous solution treatment process. Most preferably, less than about 0.1% leakage of PVA or immobilized substances from the gel beads after one week of use in an application such as an aqueous solution treatment process.
[0018] In certain preferred embodiments, including those in the paragraph above, the gel beads have a viscosity of about 0.03 kg / cm 2 More preferably, the gel beads have a hardness of about 0.1 kg / cm 2 and most preferably the gel beads have a hardness of about 0.5 kg / cm 2 In some embodiments of the present invention, the hardness is about 0.03 kg / cm or more. 2 A hardness of this magnitude can improve processability.
[0019] In certain preferred embodiments, including those in the above two paragraphs, gel beads that pass the stress test preferably have less than about 5% to less than about 10% leakage or loss of PVA or immobilized substance, more preferably have less than about 1% leakage or loss of PVA or immobilized substance, and most preferably have no measurable leakage or loss of PVA or immobilized substance. One such stress test is a velocity gradient (G≧300 s) generated by vigorous agitation with a coarse air bubble for one week. -1) is used. Additional stress tests that mimic or relate to certain applications can also be applied, using gel beads to measure leakage or loss of PVA from the beads over a period of time. Leakage and loss of PVA from the gel beads can be obtained, for example, by measuring the PVA in solution, observing the gel beads in solution, observing foaming, or measuring the COD (chemical oxygen demand), for example in reverse osmosis purified water.
[0020] Applications of embodiments of the present invention include, by way of example, the use of PVA and / or PU / PVA gels or gel beads in various substrate and aqueous solution treatments, purification processes, and manufacturing processes. These applications include applying the gels or gel beads of the present invention to substrates and aqueous solutions or mixing them together. The gels or gel beads contain immobilized substances such as, for example, microorganisms (e.g., bacteria, algae, fungi, protozoa, etc.), cells, enzymes, and / or other materials (e.g., non-enzymes, other organisms, other chemicals such as soil, sludge, purified / partially purified, or unpurified mixtures of materials). These applications include, for example, reducing COD (chemical oxygen demand), reducing volatile organic chemicals, reducing odors, denitrifying, nitrifying, and / or purifying aqueous solutions or producing products. One skilled in the art will appreciate that the application and combination of the gels and gel beads of the present invention to these substrates and aqueous solutions may be, for example, in-situ or incorporated into reaction tanks, reaction plates, reaction columns, other reaction media (vessels, tubes, etc.), and processes, and / or into existing manufacturing and purification type processes and equipment. Thus, the method includes applying the gel or gel beads containing the immobilization material to a substrate, gas, or aqueous solution, treating the substrate, gas, or aqueous solution with the gel or gel beads, and recovering (e.g., capturing, reusing, recycling, separating, filtering, removing, bypassing, etc.) the gel or gel beads from the treated substrate or aqueous solution. These applications can be applied to many different types of substrate and aqueous solution treatments, including wastewater treatment, aquaculture water treatment, aquarium water treatment, chemical process solution treatment and production, manufacturing process solution treatment and production, biofuel and biodiesel production, antibiotic process solution treatment or production, and / or other pharmaceutical process solution treatment or production. Other applications of the immobilization material include immobilizing bacteria and algae, and embodiments of the present invention can be used with embodiments of the present invention that are known or will be known to those of skill in the art (e.g., device components, biosensors, bioreactors, environmental mitigation and remediation (e.g., metals, gases, toxins) applications).
[0021] The advantages of the embodiments of the present invention are described and are clear throughout the specification. For example, certain embodiments allow the use of semi-continuous and / or continuous processing using an extruder, which has not been specifically applied to the aqueous solutions involved or to such gel beads. The disclosed pre- and post-treatment modifications of the PVA-boric acid immobilization process of the material provide a more advantageous solution, with greater stability, greater strength, improved adhesive properties, less leakage, improved physical and chemical structure, environmental friendliness, economical, etc., compared to previous applications of gels and gel beads, such as applications related to wastewater treatment, which are new applications that were not previously undertaken due to the shortcomings of the gels and gel beads used. [Brief description of the drawings]
[0022] FIG. 1 is a flow chart of how the method or process of the present invention may be practiced.
[0023] FIG. 2A is a schematic block diagram of a method or process for producing gel beads containing immobilized substances (eg, microorganisms, enzymes) according to one embodiment of the present invention.
[0024] FIG. 2B is a schematic diagram of a transport mechanism in a method or process for producing gel beads containing immobilized substances (eg, microorganisms, enzymes) according to one embodiment of the present invention.
[0025] FIG. 2C is a right-side elevational view of FIG. 2B, showing a porous cover combined with a cut piece of this embodiment.
[0026] FIG. 3 shows a preferred embodiment of PVA gel beads, where decreasing the concentration of sodium chloride solution resulted in smaller bead diameters and greater hardness with increasing conductivity.
[0027] FIG. 4 shows an example in which the gel beads of the present invention were used, and the COD (chemical oxygen demand) concentration in the wastewater was reduced to less than 250 mg / L, as required by the plant, during 60 days of operation, with a removal efficiency of about 50%.
[0028] FIG. 5 shows the COD concentrations of the two systems, the suspension system (SS) and the fixed system (IS) of the embodiment of the present invention, at different influent flow rates. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0029] The present invention provides a manufacturing method for immobilizing substances in PVA and / or PU / PVA gels and gel beads. The immobilized substances can be, for example, microorganisms (e.g., bacteria, algae, fungi, protozoa, etc.), cells, enzymes, and / or other materials (e.g., non-enzymes, other organisms, other chemicals such as soil, sludge, refined / partially refined, or unrefined mixtures of substances). It can be applied to many different kinds of substrates and aqueous solutions treatment, such as aquariums, aquaculture, water and wastewater treatment, and manufacturing and production processes (e.g., biochemical, chemical, pharmaceutical industries, etc.), and in particular, the pre-treatment and post-treatment combined with the PVA-boric acid cell immobilization process can increase the surface strength of the gels and gel beads and strengthen the internal structure of the gels and gel beads. At the same time, the present invention can solve the serious adhesion problem of the gels and gel beads. Therefore, in the preferred embodiment of the gels and gel beads, they can remain dispersed in the process, conveying and / or filtering by unit operations, even in manufacturing plants, wastewater treatment, and use in various fields.
[0030] The present invention also describes a method for improving the throughput and / or mass production of gels and gel beads containing immobilized substances. In particular, a highly productive extruder (Pruesse et al., 2002), which was not previously used with aqueous solutions at room temperature, has been used to produce gel beads containing immobilized substances of the present invention. This method has the advantage of being able to continuously discharge the PVA slurry solution, whereas other techniques, such as the dripping production technique using a dripping device, can otherwise only be operated in a discrete mode.
[0031] Examples of methods for producing immobilization substance-containing gels and gel particles of the present invention include the following:
[0032] Pretreatment: provide a PVA (powder) slurry solution, add anions or compounds capable of releasing anions to the PVA slurry solution, and / or add compounds capable of performing etherification on the gel and gel beads ("etherification compounds"), such as sulfuric acid or other acids. In certain preferred embodiments, ether-type hydrophilic polyurethanes can also be added with or without heating. The PVA slurry solution must be heated to form a gel, such as a high-viscosity gel, but the chemicals added to the slurry solution mixed with chemicals may or may not be heated. Furthermore, the etherification compounds can be added after heating the PVA chemical mixed slurry solution, or before or after adding anions or compounds capable of releasing anions to the PVA slurry solution.
[0033] PVA-boric acid treatment: A gel, such as a highly viscous gel, is then formed. Microorganisms or enzymes or other substances can be added to the PVA chemical mixed slurry solution. Thus, the present invention includes an embodiment in which a forming solution of boric acid is provided and mixed (e.g., microbial mixed or enzyme mixed) substances are provided to the forming solution to form a plurality of immobilized substances in the gel.
[0034] Forming into granules or other shapes is optional: if gel beads are required, they can be formed using discrete mode dripping methods and equipment. More preferably, due to the advantageous properties of the gels provided by embodiments of the present invention, the gel beads or other shapes can be formed in high throughput, semi-continuous and continuous and efficient extrusion equipment. The gel is preferably prepared by spreading it onto a supported surface such as a board or plate for use in the process or method.
[0035] Post-treatment: providing a hardening agent and placing the gel or gel beads in a solution of cations or cation-releasing compounds, such as alkali group metal or alkaline earth metal salts. The gel or gel beads are strengthened, hardened and can be dispersed in the future working medium. Such a method can be carried out relatively simply and at low cost, preferably without adding expensive natural polysaccharides, such as sodium alginate, or exposing the immobilized material to toxic or other denaturing conditions, such as acids, aldehydes, polyvalent anions, etc.
[0036] The embodiments of the present invention can also use etherification as an alternative, for example, ether-modified PVA as a matrix with / without other internal reinforcing materials mixed together to entrap substances such as microorganisms or enzymes in the PVA gel ether beads. About 1% to about 20% PVA can be modified by adding about 0.01 to about 1% w / v sulfuric acid or another acid, an etherification compound. Also, PU can be added before or after PVA dissolution at about 90°C to about 120°C (e.g., about 0.1 to about 20% PU). These embodiments of the present invention can use significantly less PU (less than 5%) than previously used. Surprisingly, such a small amount of PU can stabilize and prevent leakage of the PVA gel from the gel beads. Instead of using sulfuric acid or another acid to etherify the PVA, it is also possible to prevent leakage of the PVA gel from the beads.
[0037] Therefore, the present invention provides any etherification modification that can prevent leakage of PVA gel in PVA gel beads. Mechanical strength can be further increased by adding reinforcement materials. Synthetic fibers (e.g., PVAc (polyvinyl acetate), PAA (polyacrylic acid), and PAM (polyacrylamide), etc.) and / or mixtures thereof, and natural fibers (e.g., algae, cellulose, pulp, cotton, linen, etc., and / or mixtures thereof) can be added individually or in any combination to further increase mechanical strength.
[0038] The esterification of the present invention can be modified by adding anions to the PVA or PU / PVA gel to increase the mechanical strength of the PVA or PU / PVA gel particles containing the immobilized material. The anions include phosphate, sulfate, and boric acid / borate at concentrations of about 0.01% to about 5%.
[0039] In the pretreatment, the heating time of the PVA slurry solution is preferably about 30 to about 90 minutes (more preferably about 60 minutes). Thus, with this pretreatment, the gel or gel beads are subjected to stress testing at the end of the gel or gel bead process for about one week or more using coarse bubble aeration or similar stress testing technique. A preferred result is that the PVA oligomer does not leak out of the gel or gel beads. The preferred stress test used was performed with a 1 liter clean air sparger, adding 100 ml of gel beads to the sparger, filling the air sparger to 1 liter with reverse osmosis (RO) water, stirring the air sparger and setting the air flow to 1000 ml / min (hence the velocity gradient G is about 300 sec -1 ). Observe the height of the accumulated bubbles and record it daily for a week. A bubble or foam height of less than 5 cm is preferred. Measuring COD to determine leakage or loss of PVA will give better stress test results. Useful tests and analyses of G are reported in "Coagulation and Flocculation in Water and Wastewater Treatment", IWA Publishing, London, Seattle, Bratby J. (2006) and are reproduced in part at the following web address (https: / / www.iwapublishing.com / news / coagulation-and-flocculation-water- and-wastewater-treatment).
[0040] In a post-treatment, after forming the PVA and / or PU / PVA gels and gel beads containing the immobilized material and removing them from the boric acid solution, the gels and gel beads can be further cured in a solution of an alkali or alkaline earth metal salt having a concentration of about 0.5 to about 25% for a time ranging between about 30 minutes to about 15 hours, preferably about 1 hour to about 5 hours. These curing metals include Li + , Na + , K + , Ca 2+ , Mg 2+ Includes Al 3+ , Fe 2+ , Fe +3 , Zn 2+ , Cu 2+ Other metal ions such as may be used. A pH of about 4 to about 9 is preferred for this process.
[0041] In one embodiment of the invention, all of the aforementioned features are implemented to produce a gel or gel bead. In other embodiments of the invention, only one or more of the aforementioned features are implemented to produce a gel or gel bead. This flexibility is provided to overall improve the properties of the gel or gel bead for a particular application, since some modifications may create weaknesses in others. In these embodiments, the methods and steps are used as an integrated solution to achieve maximum or optimal benefits with minimum drawbacks in a given application.
[0042] The present invention provides an example of a manufacturing equipment for gel and gel beads containing immobilized substances such as microorganisms and enzymes, including a heating and melting furnace, a mixing tank, a conveying mechanism, and a forming tank. The heating and melting furnace contains PVA (or PU / PVA) powder particles, water, and anions, and forms a PVA (or PU / PVA) gel after heating. The mixing tank contains the PVA (or PU / PVA) gel mixed with substances such as microorganisms and enzymes. The conveying mechanism has a pipeline, an extrusion piece, a cutting piece, and a porous cover. The pipeline has an open outlet and an inlet connected to the mixing tank. The extrusion piece is disposed in the pipeline adjacent to the outlet, the porous cover closes the outlet and has multiple openings, and the cutting piece is disposed outside the porous cover. A bead forming tank connected to the outlet of the first pipeline is filled with a boric acid solution. The PVA (or PU / PVA) slurry solution is formed into a PVA (or PU / PVA) gel in a heated dissolving tank, mixed with one or more substances (such as microorganisms or enzymes) in a mixing tank, and then conveyed through a pipeline to a bead-forming tank. The PVA (or PU / PVA) gel is continuously extruded from the opening of the porous cover to the outlet of the pipeline, and the PVA (or PU / PVA) gel extruded from the opening is cut into multiple pieces. The PVA (or PU / PVA) gel is then converted into multiple gel beads containing the immobilized substance in the boric acid aqueous solution in the bead-forming tank. If no extrusion machine is used, a dripping technique and device can be applied to the gel to form gel beads.
[0043] In certain embodiments, for mass production using an extruder, the proposed modified PVA (or PU / PVA) gel is preferably pretreated to increase its viscosity to greater than about 5000 CPS (preferably about 10000 CPS), which would be the minimum requirement for normal extruder operation for a particular extruder.
[0044] PVA or PU / PVA gels and gel beads containing this immobilization material have a variety of uses and applications, such as wastewater treatment, waste gas treatment, odor treatment, aquaculture water treatment, aquaculture circulating water treatment, process solution treatment, chemical process solution treatment and manufacturing, substrate purification, pharmaceutical (drugs (e.g. antibiotics), supplements, ingredients) production, biofuel and biodiesel production, and biochemical (enzymes, antibodies, etc.) production.
[0045] The PVA or PU / PVA gels and gel beads containing immobilization material can also improve the effectiveness of currently existing methods and processes. The PVA or PU / PVA gels and gel beads have no or low or minimal leakage and are an improvement over existing immobilization gels and gel beads. The no or reduced leakage of PVA or PU / PVA is due to the gels and gel beads of the present invention containing nanopores that allow access. For example, in an algae overgrowth environment in a pond, lake, reservoir, or river, the ammonia, nitrite, nitrate (NH4 - N, NO2 - -N, NO3 - -N) enters the gel and gel beads and is converted into nitrogen gas in the water by the bacteria inside, and ammonia and nitrite are converted into nitrate, which is absorbed together with phosphorus by aquatic plants and algae, denitrifying the water. The algae, having lost their source of nitrogen and phosphorus, gradually decrease, and the overgrowth problem is solved or reduced. The water then returns to a more environmentally acceptable state. Also, in wastewater treatment, organic compounds (COD) can be converted into CO2, and nitrogen compounds and ammonia (NH4 + ) is produced by two types of bacteria (aerobic or anaerobic) in the gel and gel particles, which convert nitrates (NO3 - ), then N 2 is converted to
[0046] Figure 1 relates to an embodiment of novel and unobvious pre- and post-treatment steps added to the PVA-boric acid immobilization method to produce the gels and gel beads of the present invention. This method can be modified to implement higher throughput and / or mass production processes by replacing the discrete drop technique with a continuously operating extruder. The different steps or operations of Figure 1 can be applied and modified depending on the desired specifications of the desired gels and gel beads to provide improved physical and chemical structural attributes and properties.
[0047] In the pretreatment embodiment of the present invention, the outer surface and / or inner structural properties of the gel and gel beads are properties that can be improved. For example, the PVA-boric acid method can poison microorganisms or deactivate enzymes over time. The present embodiment allows the immobilization process to be less harsh, expanding the application of immobilization techniques that were previously inaccessible to different materials. It is also hypothesized that the leakage of PVA using this PVA-boric acid method is due to the fragility of the outer surface of the PVA gel beads. Therefore, prepolymerization using anions for esterification of PVA oligomers to increase the strength of the inner structure is an optional preferred embodiment. Several chemical reactions can be used, such as etherification of PVA with sulfuric acid at a temperature of about 120°C, or using heated or unheated ether-based PU copolymers to encapsulate the weak points of droplet-like tip leakage when using the dripping technique, or leakage by cutting pieces on both sides when using an extruder, etc.
[0048] During gel formation in embodiments of the present invention, there are several ways to increase the viscosity of the gel (e.g., PVA gel), and for extruders that can be operated in semi-continuous or continuous modes, as opposed to intermittent drip techniques, higher viscosities allow for higher throughput and / or mass production procedures to be successfully performed.
[0049] In post-treatment embodiments of the present invention, cations can be added to enhance and improve the surface properties of, for example, phosphate-treated gels and gel beads. These cations can aid in the stability of and / or improve the surface of, for example, gels and gel beads (e.g., PVA gel beads) by increasing sealing and / or hardness. More stable and / or improved surface properties can reduce or eliminate potential adhesion issues that may apply to such gels and gel beads.
[0050] The subject matter of the present disclosure will now be described with reference to the following examples, which are provided for illustrative purposes only, and the subject matter is not limited to these examples, but rather includes all variations evident as a result of the teachings provided herein.
[0051] Example 1
[0052] FIG. 1 shows the PVA-boric acid process, which can use either the dripping technique and equipment or the extrusion technique and equipment, and can be combined with the pre-treatment 20 and post-treatment 40 and 50 of the present invention. An aqueous solution (500 g) 10 containing 10% by weight of PVA (saponification rate 99%, polymerization degree 2400) could be mixed with immobilized substances such as microorganisms and enzymes 30. This PVA solution was then added dropwise to a gently stirred saturated boric acid solution to form spherical PVA gel beads. The gel beads could be kept in the saturated boric acid solution for 60 minutes. The beads could then be removed from the saturated boric acid solution by a screener, rinsed with water, and stored in a 1-liter flask for further testing. To measure the diameter and hardness, 5 g of beads could be removed from the flask and the water on their surface could be removed with tissue paper. The diameter and hardness of 10 beads in each example could be measured. The diameter of the beads can be measured using a digimatic caliper. Hardness is defined as the pressure applied to change the diameter of the gel beads by 50% and was measured with a force gauge (IMADA model DPX-2TR). The diameter of the beads is between about 3 and about 5 mm in all of these embodiments.
[0053] Example 2
[0054] FIG. 2A is a schematic block diagram of a process for producing gel beads containing an immobilization substance (e.g., microorganism or enzyme) according to one embodiment of the present invention. FIG. 2B is a schematic diagram of a conveying mechanism in a method or process for producing gel beads containing an immobilization substance according to one embodiment of the present invention. FIG. 2C is a right front view of FIG. 2B, showing a porous cover combined with a cut piece of this embodiment. Referring to FIG. 2A-FIG. 2C, the manufacturing apparatus 100 of the immobilization substance of this embodiment includes a heating dissolution tank 110, a mixing tank 111, a conveying mechanism 120, and a bead formation tank 130. The heating dissolution tank 110 is suitable for containing PVA and / or PU / PVA gel and a compound capable of releasing anions. The mixing tank 111 is suitable for containing PVA and / or PU / PVA gel together with substances such as microorganisms, enzymes, or other materials for immobilization.
[0055] The conveying mechanism 120 has a pipeline 121, an extrusion piece 122, a cutting piece 123, and a porous cover 124. The pipeline 121 has an outlet 125 and an inlet 126 connected to the heating dissolving tank 110 and the mixing tank 111. The extrusion piece 122 is disposed within the pipeline 121 and can be driven to approach the outlet 125. The porous cover 124 blocks the outlet 125 and has a plurality of openings 127, and the cutting piece 123 is disposed outside the porous cover 124.
[0056] In this embodiment, the pipeline 121 may be L-shaped, and the conveying mechanism 120 includes a buffer chamber 128 connected to the pipeline 121 and used to accommodate the extrusion piece 122. The buffer chamber 128 includes a power unit 1281 and a plunger rod 1282 connected between the power unit 1281 and the extrusion piece 122. The extrusion piece 122 could be a plate corresponding to the diameter of the pipeline 121. When a certain amount of PVA and / or PU / PVA gel accumulates in the pipeline 121, the extrusion piece 122 can be driven into the pipeline 121 by the power unit 1281 to extrude the PVA and / or PU / PVA gel from the pipeline 121 to the porous cover 124. After the extrusion is completed, the extrusion piece 122 can return to the buffer chamber 128. However, the present invention is not limited thereto. The pipeline 121 is not limited to an L-shape, and the extrusion piece 122 may be arranged in the pipeline 121 in other ways.
[0057] In this embodiment, there may be multiple cutting pieces 123, each cutting piece 123 including a rotating shaft 1230 and multiple blades 1231 connected to the rotating shaft 1230. As the rotating shaft 1230 of each cutting piece 123 rotates, the blades 1231 can slide through the openings 127 in the porous cover 124 and cut the PVA and / or PU / PVA gel extruded from the openings 127 into multiple sections. The rotating shaft 1230 may be connected to a motor (not shown) and a controller (not shown), such as a microcomputer, in cooperation with the operation of the extrusion piece 122. However, the present invention is not limited thereto, and the cutting pieces 123 may have other forms.
[0058] In this embodiment, the bead formation tank 130 is connected to the outlet of the pipeline 121. As can be seen from the above, the bead formation tank 130 is suitable for being filled with an aqueous boric acid solution. The multi-section PVA and / or PU / PVA gel can form a plurality of gel beads containing the immobilization substance in the aqueous boric acid solution of the bead formation tank 130.
[0059] The apparatus 100 for producing gel beads containing immobilized microorganisms or enzymes (or other substances) includes a bead hardening tank 140 disposed next to the bead formation tank 130 and connected to the bead formation tank 130. The bead hardening tank 140 is suitable for receiving gel beads containing immobilized substances from the bead formation tank 130. The bead hardening tank 140 contains the hardening solution described above, and the gel beads containing immobilized substances can be dispersed and hardened in the hardening solution. The gel beads in which microorganisms, enzymes, etc. are immobilized need to be separated from the boric acid aqueous solution before being put into the bead hardening tank 140, and a sieving device (not shown) is used to separate the boric acid aqueous solution from the gel beads containing immobilized microorganisms or enzymes (or other substances) and recover them. A liquid discharge device (not shown) can be disposed in the sieving device to recover the boric acid aqueous solution in the bead formation tank 130.
[0060] In this embodiment, the apparatus 100 for immobilizing microbial gel bead particles includes a medium tank 150 disposed next to the bead hardening tank 140. The medium tank 150 contains a medium and is adapted to receive gel beads containing immobilized microorganisms, enzymes or other substances from the bead hardening tank 140. The specific immobilized substance available, such as the microorganisms immobilized in the gel beads, can be further cultured in the medium tank 150. The gel beads with immobilized microorganisms, enzymes, etc. can be stored in the medium tank 150 before being sold.
[0061] The demonstration of the embodiment of the present invention was carried out at a local machine development factory. First, anions (NaH2PO4, Na2HPO4, MgSO4, and H2SO4, respectively) and PU were added to the PVA slurry solution to increase the viscosity (see Table 1) and form a PU / PVA gel, which was rapidly formed into immobilized microorganisms or enzyme gel beads in a bead-forming solution containing 7% boric acid and phosphate. Then, the immobilized microorganisms or enzyme gel particles formed in the particle-forming solution were put into many different particle hardening solutions, which consisted of 1% sodium chloride, ammonium chloride, ammonium sulfate, or sulfuric acid, respectively. After the immobilized microorganisms or enzyme gel beads were immersed in the particle hardening solution for a certain period of time (5 hours), the particles became hard and the particle adhesion phenomenon disappeared. [Table 1]
[0062] The results in Table 1 show that the extruder works well when the PVA or PU / PVA gel has a viscosity above about 1810 CPS. Factors that affect the viscosity include the concentration of PU and PVA, the concentration of disodium hydrogen phosphate, the storage time of the gel, and the degree of saponification. Lots No. 13-14 could form small gel beads less than 1 mm in size, which were too small for practical application in some wastewater treatment. These small beads could be made into fibers and used in precoated filters for treating aquarium water. The twin-screw extruder can make the viscous gel into larger beads. Lot No. 23 could be formed into large beads that could be used directly for wastewater treatment, as shown in Table 2.
[0063] The results in Table 2 show PVA gels with immobilizing agents in different curing solutions with a concentration of 1%. After the gel beads swell in water, the cylindrical shape of the gel beads changed to spherical. The addition of sulfuric acid (Lot No. 52) to the surface of the PVA gel beads prevented adhesion problems and allowed the gel beads to be well dispersed. In this embodiment, chloride was confirmed to make the bead surface whiter. Sulfate made the gel beads more translucent compared to certain other curing solutions. In some embodiments, "whiter" means that the surface of the PVA gel beads is more condensed than "translucent". In this example, all curing agents showing positive improvement are acceptable curing solutions and are representative embodiments. The gel beads of Lot No. 51 had a viscosity of 0.037 kg / cm 2 and a size of 4.50±0.383mm. [Table 2]
[0064] Example 3
[0065] This example shows the appearance of PVA gel beads. Here, 1% sulfuric acid (3.06 g concentrated sulfuric acid, 98%) and 10% PVA (30 g) were added to reverse osmosis water to prepare 300 ml of the new method PVA slurry solution, as shown in Tables 3 and 4. In Table 3, NaCl was used as the hardening solution, which is a significant improvement from the gel beads disclosed in U.S. Provisional Application No. 63003516 (April 2020), which is incorporated herein by reference. There, pretreatment with sulfuric acid caused the gel beads to become larger than usual, soft, and translucent, showing a weak physical structure. However, these shortcomings can be corrected by embodiments of the present invention, such that the color is observed to be whiter when the hardening cation concentration is increased beyond 0.5%. The results in Table 4 show a similar experiment, except that ammonium chloride (NH4Cl) was used in the hardening solution instead of NaCl. Ammonium chloride was able to whiten the gel beads even in as little as 0.1%. Both hardening solutions, NaCl or NH4Cl, were able to disperse gel beads in water with an average diameter of 3.22 mm ± 0.028 and a hardness of 0.017 kg / cm 2 This was achieved. [Table 3] [Table 4]
[0066] Example 4
[0067] In this example, unheated neutral ether PU was added to the heated or unheated PVA slurry solution, so that the leakage of PVA oligomers from the PVA gel beads did not occur in the aeration stress test with coarse bubbles. Table 5 shows that 6.7% PVA and 18% PU, when cured with phosphate and NaCl, can produce a white glossy surface with a hardness of only 0.005 kg / cm. 2It was shown that the PVA gel was more viscous than the PVA gel. In lot #94, even when the curing step was omitted, there was no leakage of PVA oligomers in the stress test. Table 6 showed that when the PU was heated and added to the PVA slurry solution, the gel beads shrunk significantly in the bead-forming solution. The PVA gel mixed with the heated PU became opaque and viscous like a paste (viscosity of 5080 CPS measured under similar pretreatment conditions as lot #11). The appearance is also reflected in the rotation speed of the peristaltic pump used in the dripping technique of gel bead production. Table 6 also showed that the size of the PVA gel beads with heated PU changed from 2.7 mm to a larger 4 mm. Compared to the PVA gel beads with unheated PU, these gel bead examples made from heated PU had discolored surfaces and softer gel beads. As a result, the exemplary embodiment with unheated PU provided different and more advantageous results for some applications compared to heated PU. As shown in Table 7, Lot No. 104, 12% PVA with 2.75% unheated PU also showed good properties of PVA gel beads. [Table 5] [Table 6] [Table 7]
[0068] Example 5
[0069] In this embodiment, the PVA gel beads pretreated with NaH2PO4 and treated with the PVA-boric acid method were transferred separately to various concentrations of NaCl aqueous solutions of 0.5, 1, 2, 3, 4, 5, 10, 20, and 25% and left therein for 60 minutes. These beads were then removed from the solution and rinsed with water. The diameter and hardness of 10 PVA beads from each group were measured. The remaining beads were placed in a 1000 mL air sparger for aeration stress test. During aeration, the beads were aerated with 1000 mL / min of air for one week, and then the beads were removed for physical property measurement. Figure 3 shows that as the conductivity of the sodium chloride solution in a small amount of sodium chloride increased, the diameter of the PVA gel beads decreased and the hardness increased. However, when the concentration of the sodium chloride solution was higher than 5% in these embodiments, the opposite trend occurred. The appearance of the beads is also listed in Table 8. After the aeration stress test, beads cured in solutions with concentrations between 0.5 and 25% maintained their white spherical shape. Beads cured in solutions with a concentration of 0.5% became translucent after aeration, indicating a weak physical structure of these particular PVA gel beads. Beads cured in solutions with concentrations of 5% or higher adhered to each other after the aeration stress test. Therefore, sodium chloride with a concentration between 1 and 5% (minimum 1%) is preferred for curing when using this optional post-treatment. These gel beads have some leakage of microorganisms from the gel beads. [Table 8]
[0070] The properties of the gel beads in this example were improved by using PU, an etherified compound and / or an anion or anion releasing compound in the manufacture of the gel beads.
[0071] Example 6
[0072] In this embodiment, the PVA gel beads pretreated with NaH2PO4 and treated with PVA-boric acid were transferred separately to aqueous hardening solutions of KCl at various concentrations of 0.5, 1, 2, and 3% and left therein for 60 minutes. Table 9 shows that the diameter of the beads decreases with increasing conductivity of the KCl solution, and the hardness of the beads also increases. After the aeration stress test, the beads hardened in solutions with at least 1% concentration maintained a white spherical appearance. However, the beads hardened in the 0.5% concentration solution became translucent after the aeration stress test. These gel beads have some leakage of microorganisms from the gel beads. [Table 9]
[0073] The properties of the gel beads in this example were improved by using PU, an etherified compound and / or an anion or anion releasing compound in the manufacture of the gel beads.
[0074] Example 7
[0075] In this embodiment, PVA gel beads pretreated with NaH2PO4 and treated with the PVA-boric acid method were transferred separately to CaCl2 aqueous solutions of various concentrations, 0.25, 0.5, 1, 2, 3, 5, and 10%, and left therein for 60 minutes. Table 10 shows that when the concentration is lower than 3%, the particle diameter decreases and the particle hardness increases as the conductivity of the CaCl2 solution increases. After the aeration stress test, the beads hardened in solutions with concentrations of 0.5-2% kept their white spherical shape. After the aeration stress test, the hardened particles in solutions with concentrations of 0.25%, 3% and above became translucent. These gel beads have some leakage of microorganisms from the gel beads. [Table 10]
[0076] The properties of the gel beads in this example were improved by using PU, an etherified compound and / or an anion or anion releasing compound in the manufacture of the gel beads.
[0077] Example 8
[0078] In this embodiment, a pilot plant is run using the present invention. A PVA-boric acid method was used, using an aqueous solution (150 kg) containing 10% by weight PVA mixed thoroughly with a concentrated sludge solution (3 kg) containing microorganisms (sludge concentration >6 g / L). The PVA gel beads were transferred to an aqueous solution of MgSO4 with a conductivity of 155.3 mmho / cm and left there for 90 minutes. The beads were then removed from the solution and rinsed with water. The hardness of the beads was 0.44 kg / cm. 2 The average diameter of the beads was 3.14 ± 0.08 mm.
[0079] In this example, 150 kg of beads were loaded onto a 3.2 m 3 The treated wastewater was discharged from an industrial wastewater treatment plant. The target wastewater COD (chemical oxygen demand) concentration for the advanced treatment was 250 mg / L or less, which was used to ensure the Industrial Management Center's effluent standard of 480 mg / L or less. The water pressure retention time was 20 to 24 hours. The reaction was carried out outdoors without temperature or pH control.
[0080] Figure 4 shows that the COD concentration in the wastewater was reduced to about 250 mg / L as required by the plant during 60 days of operation, and the removal efficiency finally reached 50%. The COD removal efficiency was defined as the ratio of the amount of COD removed to the total COD in the wastewater. During the test, 10 beads were removed from the system every day to measure the hardness. The hardness of the beads was 0.43 kg / cm after 4 days. 2 from 0.23kg / cm 2 However, the hardness of the beads increased to 0.41 kg / cm on the 8th day and then ranged from 0.40 to 0.70 kg / cm. 2After 60 days of operation, the particles retained their spherical shape and surface strength.
[0081] One field test failed due to dissolution of the PVA gel beads. In the second trial, post-treatment using MgSO4 was employed. These gel beads still had leakage of PVA from the gel beads (less than 5%), which was not evident in the wastewater. However, foaming could be observed in the stress test to see if there was leakage. It was observed that without the sulfuric acid or PU step in the pre-treatment, about 12 cm of foaming occurred during the stress test. On the other hand, for the gel beads pre-treated with sulfuric acid or PU according to one embodiment of the present invention, foaming was less than 1 cm in the stress test. This indicates that the pre-treatment of the present embodiment minimized leakage.
[0082] Example 9
[0083] In another test plant embodiment, the PVA-boric acid method was used with immobilized sludge as in Example 8, except that the gel beads were transferred to a 1% NaCl solution with a conductivity of 21.5 mmho / cm and left therein for 120 minutes. The average diameter of the beads is 4.37 ± 0.22 mm. In this example, 15 kg of beads were added to one of two 100 L bioreactors for wastewater treatment testing at a petrochemical plant. The same target wastewater, IS and SS, flows from the outlet of the anaerobic system of the plant's wastewater treatment equipment. The hydraulic retention time was 8-12 hours. The reaction was carried out outdoors for 3 months without temperature or pH control.
[0084] Figure 5 shows that the immobilized gel beads can effectively remove COD even when the inlet flow rate is increased to 120 mL / min (retention time 13.8 h). The COD removal efficiency was defined as the ratio of the amount of removed COD to the total COD at the wastewater inlet. The COD in Figure 5 was first measured without filtration of suspended solids. This was corrected using 1-micron filter paper to track the trend of COD from the two different systems. In the suspension system (SS), old activated sludge was added periodically to prevent sludge from flowing out. On the other side, which includes an embodiment of the present invention, the suspended solids concentration at the outlet of the immobilized system (IS) was only 1 / 5 to 1 / 6 of the concentration in the SS. All the suspended solids discharged had to be treated for recycling or disposal using a frame filter press with added chemicals. Thus, the plant costs were significantly higher relative to the costs of chemicals and electricity in the SS. In addition, the lower production of suspended solids in the IS made the disposal of suspended solids more cost-effective.
[0085] Figure 5 shows the difference in COD, the water discharge outlet, between IS and SS. IS always had a higher COD than SS. Initially, it was hypothesized that the COD of IS was due to microbial leakage from the gel beads. It was visible to the naked eye. However, when the COD data was checked, which was pretreated with various sizes of filtration before measurement, it was found that the COD caused by PVA leakage was only about 50mg / L. In this example, the water discharge standard could be achieved, but the leakage of the gel and gel beads was found to be not ideal. In some cases, this leakage could cause the system to be inoperable. For example, a biology lab using zebrafish to perform genetic experiments needed to denitrify the water to keep the fish healthy. The leakage of these gel beads is harmful to the fish. To ensure that the gel and gel beads were not leaking, it was necessary not only to clean the water but also to keep the fish alive.
[0086] Thus, the properties of the gel beads discussed in this example for plant treatment and zebrafish are improved by application of the PU, etherified and / or anionic or anion releasing compounds of the present invention.
[0087] Example 10 In this embodiment, unheated PU / PVA gel beads were used to cultivate algae, nitrifiers from a local petrochemical activated sludge system, and pure denitrifier cultures purchased from Azoo (New Taipei City, Taiwan). The composition of the PU / PVA gel beads was 10% PVA (36 g) and 2.3% PU (15 g at 55% solids) in a mixture of 285 mL reverse osmosis water and 60 mL microbial solution (2 g / L). The results showed that the algae grew within 2-3 days. The nitrifier culture showed a pink color at the bottom of the tank. Urea supplied at 800 mg / L was fully utilized with a 1-liter air sparger during the 3-day fed-batch culture. The denitrification process released nitrogen, and the PU / PVA gel beads floated to the water surface. The concentration of NO3 was fully utilized in the 2-day fed-batch culture. This is evidence that the improvement in the physical and chemical structure of the PU / PVA gel beads of the present invention does not have the previous drawbacks and enables the mass transfer capability of immobilized substances such as microorganisms used in the biological field.
[0088] literature
[0089] 1. Dumitriu, S. and Chornet, E., Processes with immobilized enzymes and cells. In “Bioconversion of waste materials to industrial products.” Martin, AM (Ed.) New York: Springer, Pages 29-102, 1998.
[0090] 2. Kuraray Co., Ltd., Shaped article made of porous hydrogel, method for producing the same and use thereof. TW201332640 A1, 2012.
[0091] 3. Aslam, M., Kalyar, M. A., Raza, Z. A., Polyvinyl Alcohol: A Review of Research Status and Use of Polyvinyl Alcohol Based Nanocomposites. Polymer Engineering and Science.58:2119-2132, 2018.
[0092] 4. Hashimoto, S and Furukawa, K., Immobilization of activated sludge by PVA-boric acid method. Biotechnology & Bioengineering. 30(1):52-9, 1987.
[0093] 5. Yao, L. and Swords, G.A., Hydrogel and methods of making and using same. US Patent: 6,268,405 B1, 2001.
[0094] 6. Ariga, O., Takagi, H., Nishizawa, H., Sano, Y., Immobilization of microorganisms with PVA hardened by iterative freezing and thawing. Journal of Fermentation Technology. 65:651-658, 1987.
[0095] 7. Shinozaki, A. and Abe, K., Microorganism immobilized in a gel prepared from polyvinyl alcohol and a polysaccharide. US Patent: 5,034,324, 1991.
[0096] 8. Chen, K.-C. and Lin, Y.-F., Immobilization of microorganisms or enzymes in polyvinyl alcohol beads. US Patent: 5,290,693, 1994.
[0097] 9. Kitano, K., Production of microorganism-immobilized support. Japan Patent: JPS645491A, 1987.
[0098] 10. Van Dinh, P. and Bach, L.T., Immobilized bacteria by using PVA (Polyvinyl alcohol) crosslinked with Sodium sulfate. The International Journal of Engineering Science.,7(1):41-47, 2014.
[0099] 11. Schmidt, A., Balle, G., Eisfeld, K., Ether of polyvinyl alcohol. US Patent: 1,971,662, 1934.
[0100] 12. Pruesse, U., Jahnz, U., Wittlich, P., Breford, J., Vorlop, K.-D., Bead production with JetCutting and rotating disk / nozzle technologies. Federal Research Center for Agriculture (FAL)- Brunswick (eds.), Voelkenrode Agricultural Research, special issue 241, pp.1-11, 2002.
[0101] 13. Huang, S.W., New method for producing immobilized microorganisms gel beads. US provisional: 63003516, Apr. 1, 2020.
[0102] 14. Hwang, S-.C., Lin, Y.H., Ho, Ho, H-.Y., Method for producing immobilized microorganisms gel beads. US provisional: 62856328, Jun. 3, 2019.
[0103] 15. Hwang, S-.C.J., Chang, H.M., Hsu, T.H., Treatment of the waste gas containing toluene and ethyl acetate by airlift bioreactor with PU / PVA immobilization cell beads. CHU-94-TR-05, 2005.
[0104] 16. Hwang, S-.C.J., Lin, Y.H., Chen, P.A., Lee, M.C., Ho, H.Y., Wu, J.Y., Development of a novel microbial immobilization method using anionic polyurethane, R.O.C. Patent: I425050, Feb. 1, 2014.
[0105] 17. Wu PF, Teng JC, Lin YH, Hwang SCJ, Increasing algal biofuel production using Nannocholorpsis oculata cultivated with anaerobically and aerobically treated swine wastewater. Bioresource Technology. 133, p.102-108, 2013.
[0106] 18. Chen KC, JY Wu, DJ Liou, SCJ Hwang, Decolorization of the textile dyes by newly isolated bacterial strains. Journal of Biotechnology. 101 (1), 57-68, 2003.
[0107] 19. Chen KC, JY Wu, CC Huang, YM Liang, SCJ Hwang, Decolorization of azo dye using PVA-immobilized microorganisms. Journal of Biotechnology .101 (3), 241-252, 2003.
[0108] 20. Chen KC, JY Wu, WB Yang, SCJ Hwang, Evaluation of effective diffusion coefficient and intrinsic kinetic parameters on azo dye biodegradation using PVA‐immobilized cell beads. Biotechnology and Bioengineering. 83 (7), 821-832, 2003.
[0109] 21. Wu JY, SCJ Hwang, CT Chen, KC Chen, Decolorization of azo dye in a FBR reactor using immobilized bacteria. Enzyme and Microbial Technology. 37 (1), 102-112, 2005.
[0110] 22. Wu JY, KC Chen, CT Chen, SCJ Hwang, Hydrodynamic characteristics of immobilized cell beads in a liquid-solid fluidized‐bed bioreactor. Biotechnology and Bioengineering. 83 (5), 583-594, 2003.
[0111] 23. He SY, YH Lin, KY Hou, SCJ Hwang, Degradation of dimethyl-sulfoxide-containing wastewater using airlift bioreactor by polyvinyl-alcohol-immobilized cell beads. Bioresource Technology. 102 (10), 5609-5616, 2011.
[0112] 24. Lin YH, SCJ Hwang, WC Shih, KC Chen, Development of a novel microorganism immobilization method using anionic polyurethane. Journal of Applied Polymer Science. 99 (3), 738-743, 2006.
[0113] 25. Hwang SCJ, JY Wu, YH Lin, IC Wen, KY Hou, SY He, Optimal dimethyl sulfoxide biodegradation using activated sludge from a chemical plant. Process Biochemistry. 42 (10), 1398-1405, 2007.
[0114] 26. Lin YH, SCJ Hwang, JY Wu, FY Chang, KC Chen, Simultaneous removal of carbon and nitrogen from swine wastewater using an immobilized-cell reactor. Journal of Environmental Engineering. 132 (3), 423-429, 2006.
[0115] 27. Hwang SCJ, YH Lin, KS Huang, JY Lyuu, CT Hou, HH Chen, SY He, Treatment of acetone waste gases using slurry-phase airlift embedded with polyacrylamide-entrapped cell beads. Journal of the Air & Waste Management Association. 59 (10), 1230-1238, 2009.
[0116] 28. Lin YH, HT Lee, HY Yin, SCJ Hwang, Method for producing butyric acid, butanol and butyrate ester. US Patent 9,371,548, 2012.
[0117] 29. He SY, SCJ Hwang, YH Lin, KY Hou, Treatment of dimethyl-sulfoxide-containing optoelectronics wastewater using airlift bioreactor with PVA-immobilized cell beads. Chemical, Biological And Environmental Engineering. 156-160, 2010.
[0118] Although the present invention has been described with reference to teachings, examples, and preferred embodiments, those skilled in the art can readily ascertain its essential features and can make various changes and modifications of the present invention to adapt it to various applications and conditions without departing from the spirit and scope of the present invention. Those skilled in the art will recognize, or be able to ascertain using no more than routine experimentation, many equivalents to the specific embodiments of the invention described herein. Such equivalents are within the scope of the present invention.
[0119] All publications, patents, and applications mentioned herein are hereby incorporated by reference.
Claims
1. 1. A method for producing a gel or gel beads containing one or more immobilization substances without the addition of alginic acid and its salts, comprising: (a) forming a slurry solution of polyvinyl alcohol (PVA) containing one or more ether-type compounds (PVA slurry solution); (b) mixing the one or more immobilization substances into the PVA slurry solution; (c) mixing a boric acid solution with the mixture of the PVA slurry solution and the one or more immobilization substances to form a PVA gel or PVA gel beads containing one or more immobilization substances; (d) mixing one or more curing agents into the PVA gel or PVA gel beads containing the one or more immobilization substances; The step (a) comprises: (a1) mixing the PVA solution with an ether-type polyurethane (PU); and / or (a2) mixing a PVA solution into sulfuric acid; The immobilization material is selected from the group consisting of microorganisms, cells, enzymes, sludge, and mixtures of these materials; A method for producing a gel or gel beads containing one or more immobilized substances.
2. 10. The method of claim 1, wherein step (a) further comprises adding one or more anions or anion releasing compounds to the PVA slurry solution.
3. The method of claim 2 , wherein the one or more anions or anion-releasing compounds include sulfate, phosphate, and / or borate anions.
4. 10. The method of claim 1, wherein forming the PVA gel or the PVA gel beads in step (c) can be performed by a dropper, an extruder, or by coating on a surface.
5. The method of claim 1 , wherein the one or more hardening agents comprise alkali metals, alkaline earth metals, other metal ions, and / or mixtures thereof.
6. The alkali metal is Li + , Na + , K + and / or mixtures thereof.
7. The alkaline earth metal is Ca. 2+ , Mg 2+ and / or mixtures thereof.
8. The other metal ion is Al 3+ , Fe 2+ , Fe 3+ , Zn 2+ , and Cu 2+ and / or mixtures thereof.
9. 10. The method of claim 1, further comprising the step of: (e) mixing one or more reinforcing agents into the PVA gel or PVA gel beads containing the one or more immobilization substances.
10. 10. The method of claim 9, wherein the one or more reinforcing agents comprise at least one of synthetic fibers selected from the group consisting of polyacrylic acid, polyvinyl acetate, polyacrylamide, and mixtures thereof, and natural fibers selected from the group consisting of algae, cellulose, pulp, cotton, linen, and mixtures thereof.
11. (A) producing a gel or gel beads containing one or more immobilized immobilization substances that can be used for purification of a substrate by the production method described in claim 1; (B) purifying the substrate using the gel or gel beads containing the one or more immobilized substances produced in (A); (C) recovering the gel or gel beads containing the immobilized substance from the substrate purified in step (B); Methods for purifying substrates.
12. A method for treating an aqueous solution, comprising the steps of: including wastewater treatment, aquaculture water treatment, aquarium water treatment, chemical process solution treatment and production, manufacturing process solution treatment and production, biofuel and biodiesel production, antibiotic process solution treatment or production, and / or other pharmaceutical process solution treatment or production; (A) producing a gel or gel beads containing one or more immobilized substances that can be used in the aqueous solution treatment method by the production method according to claim 1; (B) using the gel or gel beads containing the immobilization material produced in step (A) to reduce chemical oxygen demand, reduce odor, treat aqueous solutions by denitrification, nitrification, and / or purify aqueous solutions; (C) recovering the gel or gel beads containing the immobilization substance from the aqueous solution treated in the (B) step; Aqueous solution processing methods.
13. (A) producing a gel or gel bead containing one or more immobilized substances that can be used in a gas treatment method by the method of claim 1; (B) treating and / or purifying gas by reducing volatile organic compounds and reducing odors using the gel or gel beads containing the immobilization material produced in (A); (C) recovering the gel or gel beads containing the immobilization substance from the gas treated in the (B) step; Gas treatment methods.
14. (A) producing a gel or gel bead comprising one or more immobilized substances capable of reducing odor from an odorous substrate by the method of claim 1; (B) treating the odorous substrate by reducing the odor using a gel or gel beads containing the immobilization material produced in (A); and (C) recovering the gel or gel beads containing the immobilized substance from the odorous substrate treated in step (B); A method for treating odor from an odorous substrate.
15. A crosslinked PVA unit, one or more immobilization materials selected from microorganisms, cells, enzymes, and sludge; one or more ether type compounds, The size is between 3 mm and 5 mm, The hardness is 0.03 kg / cm 2 or more, After one week of use of the gel beads in application, there is less than 10% leakage of PVA or immobilization material from the gel beads. Gel beads free of alginic acid and its salts for use in the field of application.
16. The gel beads of claim 15, wherein the one or more ether-type compounds include ether-type PU, ether-type PVA or a combination thereof.
17. PVA, one or more immobilization substances; one or more ether type compounds, The immobilization material is selected from the group consisting of microorganisms, cells, enzymes, sludge, and mixtures of these materials; Gels or gel beads that are free of alginic acid and its salts.
18. The gel beads of claim 17, wherein the one or more ether-type compounds include ether-type PU and / or ether-type PVA.
Citation Information
Patent Citations
Method for realizing synchronous PND-DNRA treatment of wastewater containing carbon and nitrogen by immobilized beads
CN110092482A
Immobilization of enzyme and microorganism
JP1991083585A
Shrink indicator and manufacturing method therefor
JP2003305110A